1995
DOI: 10.1111/j.1365-2796.1995.tb01160.x
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency and iron overload in Swedish male adolescents

Abstract: Iron stores, as measured by serum ferritin, are small in young men studied at the end of their growth spurt. However, iron deficiency is rare. Therefore, the present study has not been able to confirm the high prevalence of iron deficiency recently reported. A prevalence of genetic haemochromatosis of 0.4%, confirms earlier findings and would mean that 12.6% of the population are heterozygotic carriers of the iron-loading genes. These findings give no support for a proposed, more effective iron-enrichment of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1
5

Year Published

1996
1996
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 31 publications
2
17
1
5
Order By: Relevance
“…Using a study design similar to ours, Olsson et al [9] reported a 0-5% prevalence of anemia and .17% prevalence of iron deficiency in male Swedish military recruits. The authors attributed the low rate of anemia to the highly iron-fortified Swedish diet.…”
Section: Discussionmentioning
confidence: 85%
“…Using a study design similar to ours, Olsson et al [9] reported a 0-5% prevalence of anemia and .17% prevalence of iron deficiency in male Swedish military recruits. The authors attributed the low rate of anemia to the highly iron-fortified Swedish diet.…”
Section: Discussionmentioning
confidence: 85%
“…In epidemiological studies of iron status it appears relevant to define and include those subjects having small and nearly depleted iron stores into the iron deficiency risk group. However, in the clinical setting, in order to substantiate overt iron deficiency with iron deficiency anemia, the data presented by Olsson et al [13] are in favor of a critical value of 12 mg/l. In the present study the critical Amersham RIA serum ferritin values used corresponded to WHO ferritin standard values of 12, 15, and 30 mg/l [6].…”
Section: Discussionmentioning
confidence: 87%
“…However, there is some debate about which serum ferritin level should be used as the cut-off value for absent iron stores and imminent or overt iron deficiency [11]. Cook and Skikne [12] and Olsson et al [13] advocate a critical value of 12 mg/l, while Bergström et al [14] argue that the critical value in fertile women should be set at an even lower level. Milman et al [9] and Worwood [15] advocate a cut-off value of 15 mg/l, Hallberg et al [16] a value of 16 mg/l.…”
Section: Discussionmentioning
confidence: 98%
“…However, there is an increase in the prevalence of high ferritin values above 300 mg/l with age [4], and in men the problems associated with iron overload have attracted much attention during recent years. In Sweden, Olsson et al [8] reported a prevalence of genetic hemochromatosis of 0.4%, which means that 13% of the population are heterozygotic carriers of the hemochromatosis allele. In women, serum ferritin levels remain low from adolescence (menarche) to the menopause [9].…”
Section: Discussionmentioning
confidence: 97%